2014
DOI: 10.1163/17087384-12342034
|View full text |Cite
|
Sign up to set email alerts
|

Crime and Public Support for the Rule of Law in Latin America and Africa

Abstract: Crime poses a formidable obstacle to democratization in many parts of the developing world. New democracies in Central America and sub-Saharan Africa face some of the highest homicide rates in the world. Politicians, citizens, and policy-makers have raised the alarm about the growing tide of criminality. Public insecurity, coupled with inefficient and often corrupt justice systems, makes democratization uncertain. Even if new democracies do not revert to dictatorship, the quality of democracy may suffer if cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This situation is particularly evident among women, citizens with low-income and low education levels, and people living in small municipalities (Seligson et al, 2000 ). Smithey and Malone ( 2014 ) extend this claim to the aggregate level. According to their regression analysis, not only personal experiences with crime significantly reduce support for the rule of law in El Salvador but also fear of crime at the national level (Smithey & Malone, 2014 ).…”
Section: Prior Empirical Researchmentioning
confidence: 83%
See 2 more Smart Citations
“…This situation is particularly evident among women, citizens with low-income and low education levels, and people living in small municipalities (Seligson et al, 2000 ). Smithey and Malone ( 2014 ) extend this claim to the aggregate level. According to their regression analysis, not only personal experiences with crime significantly reduce support for the rule of law in El Salvador but also fear of crime at the national level (Smithey & Malone, 2014 ).…”
Section: Prior Empirical Researchmentioning
confidence: 83%
“…Smithey and Malone ( 2014 ) extend this claim to the aggregate level. According to their regression analysis, not only personal experiences with crime significantly reduce support for the rule of law in El Salvador but also fear of crime at the national level (Smithey & Malone, 2014 ).…”
Section: Prior Empirical Researchmentioning
confidence: 83%
See 1 more Smart Citation
“…Just as crime concerns have driven trends in incarceration, they also appear to be associated with attitudes towards extra-legal measures in policing. For instance, research examining citizens’ attitudes in Mexico and Central America has found that fear of crime correlates with a greater acceptance of violations of the law by police (Smithey & Malone, 2014). Moreover, crime victimization appears to be associated with tolerance of police abuse in the region as a whole (Bateson, 2012).…”
mentioning
confidence: 99%